2014
DOI: 10.1002/pssa.201330297
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent structure and magnetism of Mn‐doped Ge nanowires

Abstract: We report a study on the growth temperature dependent phase formation and its magnetic property in Mn‐doped Ge nanowires (NWs) fabricated at temperature (TG) varying from 600 to 900 °C using vapor–liquid–solid technique. Structural and magnetic measurements on the nanowires reveal that Mn are not homogeneously distributed in Ge‐matrix, but atomic clusters (Mn‐rich regions) are formed in lightly doped Ge matrix (GeMn‐matrix) at 600 °C. Upon increasing TG, Ge3Mn5 compound starts to nucleate in expense of atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Thereafter, Er 3+ ions de-excite to the 4 I 13/2 state by non-radiative relaxation from where a radiative transition to the ground state yielding emission at 1.53 μm. The PL intensity at 1.53 μm up to room temperature in Er doped Ge nanowires grown by pulsed laser deposition [26] Apart from Er, Mn doping in Ge nanostructures have also been employed in the field of diluted magnetic semiconductors [234][235][236][237]. The growth-temperature-dependent phase formation and the magnetic properties of Mn-doped Ge nanowires grown at temperatures varying from 600 to 900 °C using VLS technique have been reported [237].…”
Section: Nanowire Photo-electro Chemical Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, Er 3+ ions de-excite to the 4 I 13/2 state by non-radiative relaxation from where a radiative transition to the ground state yielding emission at 1.53 μm. The PL intensity at 1.53 μm up to room temperature in Er doped Ge nanowires grown by pulsed laser deposition [26] Apart from Er, Mn doping in Ge nanostructures have also been employed in the field of diluted magnetic semiconductors [234][235][236][237]. The growth-temperature-dependent phase formation and the magnetic properties of Mn-doped Ge nanowires grown at temperatures varying from 600 to 900 °C using VLS technique have been reported [237].…”
Section: Nanowire Photo-electro Chemical Cellsmentioning
confidence: 99%
“…The PL intensity at 1.53 μm up to room temperature in Er doped Ge nanowires grown by pulsed laser deposition [26] Apart from Er, Mn doping in Ge nanostructures have also been employed in the field of diluted magnetic semiconductors [234][235][236][237]. The growth-temperature-dependent phase formation and the magnetic properties of Mn-doped Ge nanowires grown at temperatures varying from 600 to 900 °C using VLS technique have been reported [237]. The nanowire sample grown at a low temperature (600 °C) contains atomic clusters of Mn in a GeMn-matrix and behaves like a clusterglass type of material having blocking temperature (T B )=15 K, transition temperature (T C )=108 K, and freezing temperature of 12 K. On the other hand, the sample grown at 900 °C contained only nanoparticles of Ge 3 Mn 5 in Ge-matrix without any signature of atomic clusters and behaved like interacting superparamagnetic in nature having T B =274 K and T C =293 K. This study clearly demonstrated the potential of Mn doped Ge nanowires in the application of nanoscale spintronic devices [237] Rapid industrialization and improvement of human quality of life demand sensitive and selective detection of gas molecules and biological species for environmental monitoring, process control, safety, and medical diagnostics purposes.…”
Section: Nanowire Photo-electro Chemical Cellsmentioning
confidence: 99%
“…Although most reports were focused on III-V and II-VI semiconductor based DMSs [7][8][9], IV semiconductor (for instance, Si, Ge and SiGe) based DMSs have drawn more and more attention because they can be easily integrated with the current Si-based technology. Both experimental and theoretical studies have shown that transition metal (TM) doped Si or Ge can exhibit magnetism [10][11][12][13][14][15][16][17][18][19][20]. Various experimental studies have shown that the incorporation of TMs is a key technique for modulating the magnetic properties of Si or Ge based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al have reported the fabrication of highly Mn doped Ge bulk single crystals and a FM ordering with T C of 285 K [13]. Majumdar et al have realized the Mn doped Ge NWs' growth by the vapor-liquidsolid technique and the Curie temperature reached 293 K [14]. On the other hand, theoretical studies have also predicted a lot of interesting results in different IV semiconductor based systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Mn x Ge 1−x layers could be grown on one-dimensional (1D) Si nanopillars so as to release the stress caused by the lattice mismatch between Si and Mn x Ge 1−x , and suppress the formations of the intermetallic phase, and low temperature growth could also suppress the formations of the intermetallic phase of Mn and Ge. On the other hand, various possibilities of a wide range of devices based on 1D semiconducting nanostructures have been reported for the next generation of nanoelectronics and photonics [24][25][26]. In particular, 1D FMS materials have a great potential as building blocks of spin field-effect transistors and future memory devices [27][28][29], for example, nonvolatile Mn x Ge 1−x nanowire-based spin transistors have been proposed and studied in recent years [30][31][32].…”
Section: Introductionmentioning
confidence: 99%